Industry analysis and supply chain management of Lafarge Surma Cement Ltd. - Jewel, Md. Shaijuddin (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.